STUDY ON THE CHEMICAL CONSTITUENTS AND ANTIBACTERIAL ACTIVITY OF ESSENTIAL OIL OF ACORUS CALAMUS L. RHIZOMES OF RUPENDEHI DISTRICT (NEPAL) - Joshi, Susan; Bashyal, Sundar (Journal of Institute of Science and Technology, 2019)
The essential oil from the air dried powder of wild Acorus calamus L. rhizomes was isolated using Clevenger-type hydrodistillation apparatus and its chemical constituents were analyzed by gas chromatography-mass spectrometric (GC-MS) analysis. A total numbers of fourteen chemical constituents were identified and quantified occupying 100 % of total oil composition. The major chemical constituents are reported to be β-asarone (68.96 %), 4-hydroxy-4-methyl-2-pentanone (8.73 %) shyobunone (8.65 %), p-methoxyphenyl butanone (4.16 %) and the minor chemical constituents are δ-cadinene (0.84 %), isoelemicine (2.68 %), muurolene (1.92 %) and cis-ocimene (1.44 %). The antibacterial activity of the essential oil isolated from the wild Acorus calamus L. rhizomes was carried out using paper disc method against one Gram positive bacteria of Staphylococcus aureus and three Gram negative bacteria of Escherichia coli, Klebsiella pneumoniae and Proteus vulgaris. The isolated essential oil from the dry powder of Acorus calamus L. rhizome showed a good potentiality of the antibacterial effect against tested bacteria.